Pendampingan Aparatur Gampong Keumuneng Hulu Kabupaten Aceh Timur Dalam Pembuatan Draft Qanun - Fitriani, Rini; Sahara, Siti; Bustami, Bustami; Auliaurrahman, Auliaurrahman; Zulfiani, Zulfiani (Jurnal Ilmiah Pengabdian dan Inovasi, 2022)
Gampong Qanun as legislation at the village level set by the Keuchik after being discussed and agreed with Tuha Peuet Gampong can be a guide for community life. However, the Human Resources of the Apparatus in the Keumuneng Hulu Village needed to make the Draft Gampong Qanun are not sufficient. Seeing this condition, the Community Service Team from the Faculty of Law, Samudra University needs to provide assistance to the Gampong apparatus in making the Draft Gampong Qanun. In the implementation of Community Service, the PKM Team started by conveying the socialization of the understanding and urgency of the Qanun to the Keuchik, Tuha Peut and gampong apparatus and then continued with technical guidance on how the format of the Draft Qanun should be drawn up, up to the step of assisting the village apparatus to complete the drafting of the Qanun. Gampong so that the draft Qanun is completed and submitted to the Keuchik and Tuha Peut for immediate approval.